2020
DOI: 10.1021/acs.langmuir.0c01350
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Dependent Self-Assemblies and Pyridine Modulation of a Porphyrin Molecule at Liquid/Solid Interfaces

Abstract: On the highly oriented pyrolytic graphite (HOPG) surface, a new porphyrin molecule MT-4 containing a porphine core with six alkyl chains and two carboxyl groups has been explored using scanning tunneling microscopy (STM) technology. Solvent and pyridine regulation have been proved to be two effective ways to control and tune the supramolecular structure of MT-4 at interfaces. Different high-resolution STM (HR-STM) images with highly ordered and closely packed arrangements were gained at the corresponding liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Through the co-assembly of different aromatic carboxylic acids and different pyridine molecules, a rich library of two-component nanopatterned supramolecular structures has been obtained. 33–35 In this study, three structurally distinct pyridine molecules (BPD, BPDYB and TPDYB) were introduced to co-assemble with the H 5 BHB molecule. Their chemical structures are presented in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Through the co-assembly of different aromatic carboxylic acids and different pyridine molecules, a rich library of two-component nanopatterned supramolecular structures has been obtained. 33–35 In this study, three structurally distinct pyridine molecules (BPD, BPDYB and TPDYB) were introduced to co-assemble with the H 5 BHB molecule. Their chemical structures are presented in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…12 In recent years, novel nanoconstructions of porphyrin derivatives at solid/liquid interfaces have been widely used. 13 Although more and more studies have been carried out on the assembly of porphyrin molecules on two-dimensional surfaces/interfaces, the well-ordered assembly of porphyrin derivatives needs further study. Generally speaking, whether a supramolecular self-assembly structure is stably ordered or not depends on the solvent, the type of functional group, and the interaction force between molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
“…20,21 Due to the selectivity and saturation of hydrogen bonding, an increasing number of research have reported that porphyrin with a carboxyl functional group interacts with other molecules by hydrogen bonding to form supramolecular nanostructures. 8,13,15,22 Scanning tunneling microscopy (STM) with atomic resolution is considered to be the most effective method to investigate the molecular dynamics of assembly at solid/liquid interfaces, 23−28 and the regulation behavior of guest molecules, which impact the host molecules can be observed in real-time by STM under an ambient environment. 29−34 Hou et al used STM to detect porphyrin derivatives with side chain groups not only to obtain a self-assembled structure of H 2 TCPp under the action of hydrogen bonds but also to successfully regulate the host molecule by introducing dipyridine as a guest molecule.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Host–guest coassembly is a highly efficient strategy to design accurate and controllable orderly π-conjugated architectures on solid surfaces at the molecular level system, which makes host–guest chemistry attract much attention. Host networks with rigid cavities will not be changed by guest molecules. , The host–guest architectures with the dynamic process are also observed by scanning tunneling microscopy (STM), which has developed a new way for the observation of the world at the nanometer scale. Recently, many coassembled systems on the solid/liquid interface have been investigated by the STM technique. Zhang et al reported that two shape-persistent circular molecules displayed a surprising concentration-controlled self-assembly behavior at the highly oriented pyrolytic graphite (HOPG)/liquid interface and captured C70 into the cavities to make up stable complexes . Cheng et al studied the adsorption of selectivity and competitivity with guest molecules C70 and coronene in the electron donor–acceptor-conjugated macrocycles systems.…”
Section: Introductionmentioning
confidence: 99%